ChemInform Abstract: Complex Spinel Titanate as an Advanced Anode Material for Rechargeable Lithium‐Ion Batteries. Issue 34 (26th August 2014) - Chen, Wei; Liang, Hanfeng; Ren, Weijian; Shao, Lianyi; Shu, Jie; Wang, Zhoucheng
Abstract The titanates Li2MTi3O8 (M: Zn, Cu, Zn0.5Cu0.5) are synthesized by solid state reactions of stoichiometric mixtures of TiO2, Li2CO3, Zn(OAc)2, and/or Cu(OAc)2 (750 °C, 5 h).